1996
DOI: 10.2165/00002512-199609030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Amylin, Amyloid and Age-Related Disease

Abstract: Amylin, a 37-amino acid peptide, is cosecreted with insulin from the beta-cells of the pancreatic islets in normal response to physiological stimuli. It is the major protein of islet amyloid, which is usually present in the pancreases of people with non-insulin-dependent (type II) diabetes mellitus. Amylin elicits potent effects on carbohydrate metabolism in rodent tissues, causing insulin resistance in skeletal muscle and liver. A close structural relationship exists between amylin and the 2 calcitonin gene-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Aggregation of amylin plays a role in the progress of type-2 diabetes (T2D) and in the degenerative process of β-cells. Recent computational studies have shown the specific interactions of amylin with membranes . Cross-seeding between amyloidogenic proteins, such as rat amylin and human amylin,amylin and Aβ, and amylin and the non-amyloidogenic component has also been investigated by computational studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation of amylin plays a role in the progress of type-2 diabetes (T2D) and in the degenerative process of β-cells. Recent computational studies have shown the specific interactions of amylin with membranes . Cross-seeding between amyloidogenic proteins, such as rat amylin and human amylin,amylin and Aβ, and amylin and the non-amyloidogenic component has also been investigated by computational studies.…”
Section: Discussionmentioning
confidence: 99%
“…At high levels of glucose in the blood, amylin is cosecreted with insulin into the bloodstream and participates in glycemic control . It has a wide range of glucose-lowering effects: delaying gastric emptying, lowering postprandial glucose and postprandial glucagon, , and reducing insulin release. Aggregation of amylin has a role in the progress of type-2 diabetes (T2D) and in the degenerative process of β-cells. The main components of the extracellular amyloid deposits found in most T2D patients are amylin aggregates. These amylin aggregates include oligomers and fibrils that are formed during the self-assembly process.…”
Section: Introductionmentioning
confidence: 99%